An outline of the need for psychology knowledge in health professionals: implications for community development and breast cancer prevention - Ahmadian, Maryam; Abu Samah, Asnarulkhadi (Asian Pacific Education Press Ltd., 2014)
Knowledge of health and community psychology in health professionals influences psychosocial and community determinants of health and promoting participation in disease prevention at the community level. This paper appraises the potential of knowledge on psychology in health care professionals and its contribution to community empowerment through individual behavior change and health practice. The authors proposed a schematic model for the use of psychological knowledge in health professionals to promote participation in health interventions/disease prevention programs in developing countries. By implication, the paper provides a vision on policies towards supporting breast cancer secondary prevention efforts for community health development in Asian countries.